A Multicenter, Randomized, Double-blind, Placebo-controlled Trial of Saccharomyces boulardii in Infants and Children With Acute Diarrhea. Issue 11 (November 2020) - Mourey, Florian; Sureja, Varun; Kheni, Dharmeshkumar; Shah, Parthiv; Parikh, Devang; Upadhyay, Unmesh; Satia, Milan; Shah, Dhara; Troise, Charlotte; Decherf, Amélie
Abstract : Aim: This study was designed to assess the efficacy and safety of Saccharomyces cerevisiae variant boulardii CNCM I-3799 ( S . boulardii CNCM I-3799) in the management of acute diarrhea in children. Methods: A total of 100 infants and children 3–36 months of age with acute diarrhea received medical care according to the World Health Organization guidelines on the management of acute diarrhea in children and were randomly allocated to the probiotic group ( S. boulardii CNCM I-3799 at a daily dose of 5 billion CFU twice daily) or to the placebo group. Infants and children were treated for 5 days and an extended follow-up was planned 1 and 2 months after the end of the treatment period. Primary endpoint was the time of recovery from diarrhea defined as the duration of diarrhea. Other parameters, such as frequency and consistency of stools, associated with the severity of diarrhea episodes were defined as secondary endpoints. Results: The administration of S. boulardii CNCM I-3799 was associated with beneficial effects on duration and severity of diarrhea. The time of recovery from diarrhea was significantly shorter in the probiotic group compared with the placebo group (65.8 ± 12 hours vs. 95.3 ± 17.6 hours, P = 0.0001). Faster remission in the probiotic group was also demonstrated by a shorter time before the first episode of semisolid stool [−23.5 hours, diff (95% CI): −7.99 (−31.49 to −15.51), P = 0.0001] and the faster normalization of stool consistency. S. boulardii CNCM I-3799 was well tolerated. Conclusion: S. boulardii CNCM I-3799 supplementation in children with acute diarrhea was shown effective in reducing the duration and severity of diarrhea in infants and children.